Expanding A Tetration Expression!

Algebra Level 5

k = 1 2016 ( 1 + z k x 1 1 k ) = 1 + a 1 x m 1 + a 2 x m 2 + + a 2017 x m 2017 + + a N x m N \large \prod_{k=1}^{2016} \left (1 + z_k x^{11^k} \right) = 1 + a_1 x^{m_1} + a_2 x^{m_2} + \cdots + a_{2017} x^{m_{2017}} + \cdots + a_N x^{m_N}

Consider the expansion above for z k = e 2 k π i / 11 z_k = e^{2k\pi i /11} , where a 1 < a 2 < a 3 < < a N a_1 <a_2 < a_3 < \cdots < a_N and m 1 < m 2 < < m N m_1 < m_2 < \cdots < m_N are all constants.

If z n = a 2017 z_n =a_{2017} , find the minimum value of n n .

Clarification: i = 1 i=\sqrt{-1} .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Kartik Sharma
Sep 26, 2016

This is my favorite problem personally.

A ( x ) : = k = 1 N ( 1 + f ( k ) x b k ) = 1 + a 1 x m 1 + a 2 x m 2 + \displaystyle A(x) := \prod_{k=1}^{N}{\left(1 + f(k)x^{b^k}\right)} = 1 + a_1 x^{m_1} + a_2 x^{m_2} + \cdots

Now what actually is happening on the LHS - ( 1 + f ( 1 ) x b ) ( 1 + f ( 2 ) x b 2 ) ( 1 + f ( 3 ) x b 3 ) \displaystyle (1 + f(1)x^b)(1 + f(2)x^{b^2})(1 + f(3)x^{b^3}) \cdots

Let's move our focus to what will the power of x x be for a n a_n and then all we need to do is to multiply the corresponding f ( m ) f(m) 's that it would have been made of.

One can see that b + b 2 + b 3 + + b p 1 < b p ; b 2 \displaystyle b + b^2 + b^3 + \cdots + b^{p-1} < b^p ; \forall b\geq 2

So the powers of x x on RHS will be like

b , b 2 , b + b 2 , b 3 , b + b 3 , b 2 + b 3 , \displaystyle b, b^2, b + b^2, b^3, b + b^3, b^2 + b^3, \cdots

Or to say that before x b p x^{b^p} comes, all the combinations of b , b 2 , b 3 , b 4 , , b p 1 \displaystyle {b, b^2, b^3, b^4, \cdots, b^{p-1}} would have already come.

In other words, index at which x b p \displaystyle x^{b^p} comes is ( p 1 1 ) + ( p 1 2 ) + + ( p 1 p 1 ) + 1 = 2 p 1 \displaystyle \binom{p-1}{1} + \binom{p-1}{2} + \cdots + \binom{p-1}{p-1} + 1 = 2^{p-1}

a 2 p 1 = [ x b p ] A ( x ) \displaystyle a_{2^{p-1}} = [x^{b^p}]{A(x)}

In fact, now one can imagine that after this index the same p 1 p-1 combinations will come so as to say :

a 2 p 1 + 2 p 1 1 + 2 p 2 1 + + 2 p n 1 = [ x b p + b p 1 + b p 2 + + b p n ] A ( x ) \displaystyle \large a_{2^{p-1} + 2^{p_1-1} + 2^{p_2-1} + \cdots + 2^{p_n -1}} = [\displaystyle x^{b^p + b^{p_1} + b^{p_2} + \cdots + b^{p_n}}]{A(x)}

And since we know what all terms of LHS had had been multiplied to make up that power of x x , we can easily formulate :

a 2 p 1 + 2 p 1 1 + 2 p 2 1 + + 2 p n 1 = f ( p ) f ( p 1 ) f ( p 2 ) f ( p 3 ) f ( p n ) \displaystyle \large a_{2^{p-1} + 2^{p_1-1} + 2^{p_2-1} + \cdots + 2^{p_n -1}} = \displaystyle f(p)f(p_1)f(p_2)f(p_3) \cdots f(p_n)

We can in fact make steps to find a n a_n in such a polynomial :

  • Step 1 : Write n n in binary .

  • Step 2 : Note down the indices n i {n_i} at which 1 1 comes starting from right starting from 1 1 st index .

  • Step 3 : Multiply all the f ( n i ) f(n_i) .

Now for our given problem,

2017 = ( 11111100001 ) 2 \displaystyle 2017 = (11111100001)_2

a 2017 = z 11 z 10 z 9 z 8 z 7 z 6 z 1 \displaystyle a_{2017} = z_{11} z_{10} z_9 z_8 z_7 z_6 z_1

a 2017 = z 8 \displaystyle \boxed{a_{2017} = z_8}

I really enjoyed solving this problem! (+1). Did you create this problem or did you find it somewhere?

Aditya Dhawan - 4 years, 7 months ago

Log in to reply

I found a similar problem. Solution was not given. So, I tried to generalize.

Kartik Sharma - 4 years, 7 months ago

Maybe you had to specify "find the minimum n".

@Filippo Quattrocchi Yes, I agree. I have edited it. You could have reported it, anyways.

Kartik Sharma - 4 years, 8 months ago

Maybe you had to specify "find the minimum n non negative".

Abdelhamid Saadi - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...